1976
DOI: 10.1128/aac.10.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of Bacillus brevis ATCC 9999, the Producer of Gramicidin S

Abstract: The nutrition of the gramicidin S (GS) producer Bacillus brevis ATCC 9999 was studied with respect to growth and antibiotic production. In a complex medium containing yeast extract and peptone, only glycerol, 1)-fructose, and meso-inositol contributed to growth, whereas other hexoses, pentoses, polyols, polysaccharides, and organic acids were inactive. Glycerol and fructose were inhibitory to GS formation; inositol had no effect. In chemically defined media containing a mixture of five amino acids (glutamine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…As the next step, we therefore compared urea, ammonium chloride, and ammonium sulfate as a nitrogen source in a glycerol-containing minimal medium for A. migulanus strain DSM 5759. Only ammonium sulfate was able to support GS production, in agreement with previous observations (22) for the type strain ATCC 9999. Notably, the authors reported a yield of 100 mg/liter GS with 12 g/liter ammonium sulfate, but we also checked results with 10 and 5 g/liter and obtained the same 100-mg/liter yield independent of concentration.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As the next step, we therefore compared urea, ammonium chloride, and ammonium sulfate as a nitrogen source in a glycerol-containing minimal medium for A. migulanus strain DSM 5759. Only ammonium sulfate was able to support GS production, in agreement with previous observations (22) for the type strain ATCC 9999. Notably, the authors reported a yield of 100 mg/liter GS with 12 g/liter ammonium sulfate, but we also checked results with 10 and 5 g/liter and obtained the same 100-mg/liter yield independent of concentration.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, glucose-containing minimal media, which are generally used for uniform labeling, cannot be employed to produce GS. A. migulanus can utilize only fructose, glycerol, or inositol as a single carbon source (22); hence, only these substrates in the isotope-enriched form can be used. In the chemically defined medium with glycerol, the best nitrogen sources are ammonium phosphate, ammonium sulfate (22), or ammonium succinate (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diauxic growth observed in the cultures supplemented with amino acids is similar to that observed by Vandamme & Demain (1976) in B. brevis ATCC 9999, the GS producer strain. They found B. brevis initially grew at the expense of amino acids supplemented in the growth medium; only after a diauxic lag was the available carbon source utilized and antimicrobial peptide production initiated.…”
Section: Discussionsupporting
confidence: 80%
“…El glicerol y la D-fructosa mostraron ser inhibidores de la producción de GS, de igual forma se observó que aminoá-cidos especialmente la fenilalanina, así como otros sustratos permiten fases aceleradas en la cinética de crecimiento y producción del antimicrobiano (16).…”
Section: Bacillus Spp: Generalidadesunclassified